A kind of charcoal that can remove nanometer plastic and antibiotic in large capacity synchronously and its application

By preparing sulfur-doped biochar, the problem of simultaneous removal of nanoplastics and antibiotics was solved, achieving efficient, large-capacity, and low-cost purification of composite pollutants. It is suitable for various water quality conditions and has multi-adsorption capacity.

CN123024518APending Publication Date: 2026-11-03NANJING FORESTRY UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611157031.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies are insufficient for efficiently and simultaneously removing the combined pollutants of nanoplastics and antibiotics. Traditional methods are costly, inefficient, and pose a risk of secondary pollution. Furthermore, existing adsorbents have limited applicability and adsorption capacity for nanoplastics and antibiotics.

Method used

A sulfur-doped biochar preparation method was adopted, which involves mixing straw with potassium thiosulfate and potassium bicarbonate and calcining it under a protective atmosphere to prepare biochar with multiple affinities, which can be used for the simultaneous adsorption of nanoplastics and antibiotics.

Benefits of technology

It achieves efficient and large-capacity removal of nanoplastics and antibiotics, with low material cost, wide applicability, good stability in complex water bodies, no secondary pollution, and synergistic adsorption capacity for multiple pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123024518A_ABST
    Figure CN123024518A_ABST
Patent Text Reader

Abstract

The application discloses a kind of biological carbon that can remove nanometer plastic and antibiotic simultaneously in large capacity and application thereof, belong to water pollution control technical field.The straw is cleaned, dried, crushed and sieved, then a planetary ball mill is used to obtain straw powder;The straw powder, potassium thiosulfate and potassium bicarbonate are ground and mixed uniformly, and the mixture is placed in a tube furnace for first calcination under nitrogen atmosphere protection;After the calcination product is cooled, it is washed, filtered and dried multiple times;The dried solid product is subjected to second calcination under nitrogen protection again, and the sulfur-doped biological carbon is obtained after cooling.The biological carbon prepared by the application has an adsorption capacity of 60~300mg / g for nanometer plastic and 2.5~5mmol / g for antibiotic, can simultaneously remove various nanometer plastics and cephalosporin and sulfonamide antibiotics, and the biological carbon is resistant to negative interference of salt, humic acid and heavy metal, and has a synergistic purification effect when nanometer plastic and antibiotic coexist.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water pollution control technology, specifically relating to a biochar capable of simultaneously removing nanoplastics and antibiotics in large quantities and its applications. Background Technology

[0002] New pollutants such as micro- and nano-plastics and antibiotics have attracted significant global attention due to their strong bioaccumulation and persistent harmfulness. Plastic particles and antibiotics are widely present in various environmental media at alarming concentrations, interacting intricately to influence each other's transformation and bioavailability. A series of reports indicate that micro- and nano-plastics have become a breeding ground for antibiotic resistance genes, exacerbating the risk of horizontal transfer of these genes. The need for ensuring the quality and safety of water resources is urgent. However, traditional biochemical treatment technologies can only effectively remove micron-sized plastic particles; even smaller nano-plastics (0.001~1µm) and antibiotic molecules are poorly purified under the "protection" of complex, high-concentration natural media. Compared to nano-plastics, the development of enhanced antibiotic removal technologies is relatively abundant, but problems such as high cost, low efficiency in practical applications, and uncontrollable toxicity of intermediate products remain unresolved. Research on the retention / removal of nano-plastics has only been conducted for a few years; due to their inert polymer structure, flocculation and adsorption separation are the mainstream removal strategies. However, current reported technologies all focus on single components, with almost no reports on the simultaneous removal of nanoplastics and antibiotics. From the perspectives of economic rationality and technical simplicity, developing green and efficient methods for the simultaneous removal of complex pollutants such as nanoplastics and antibiotics is an inevitable requirement for the development of environmental functional materials in the new era. Adsorption is an important means of achieving rapid pollutant removal, with many advantages such as simplicity, low waste, and recyclability. Currently, ion exchange resins, polysaccharide gels, carbon materials modified with metal oxides, and metal-organic frameworks have been reported to have some removal capacity for negatively charged nanoplastics under ideal conditions. However, these adsorbents have limited applicability (type, water quality conditions, synchronicity) for the removal of nanoplastics and antibiotics due to their single affinity sites, limited functionality, and lack of porous and unobstructed mass transfer structures, making it difficult to meet application requirements. Summary of the Invention

[0003] The technical problem solved by this invention is to provide a biochar that can simultaneously remove nanoplastics and antibiotics in large capacity. This biochar has superior adsorption affinity and adsorption capacity for a wide range of tested antibiotics and nanoplastics. Another technical problem to be solved by this invention is to provide the application of this sulfur-doped biochar in the simultaneous removal of composite pollutants of nanoplastics and antibiotics from water.

[0004] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing biochar capable of simultaneously and in large-capacity removal of nanoplastics and antibiotics includes the following steps:

[0006] 1) After washing, drying, crushing and sieving the straw, it is ball-milled using a planetary ball mill to obtain straw powder;

[0007] 2) Grind and mix straw powder, potassium thiosulfate, and potassium bicarbonate evenly. Place the mixture in a tube furnace and calcine it once under nitrogen atmosphere protection. After cooling, the calcined product is washed, filtered, and dried multiple times.

[0008] 3) The dried solid product was calcined again under nitrogen protection, and after cooling, sulfur-doped biochar was obtained.

[0009] Furthermore, in step 1), the ball milling speed is 500 r / min and the time is 5 h.

[0010] Furthermore, in step 2), the mass ratio of straw powder, potassium thiosulfate, and potassium bicarbonate is 1:1:2.

[0011] Furthermore, in step 2), the initial calcination temperature is 900℃, the calcination time is 2h, the heating rate is 5℃ / min, and the nitrogen flow rate is 50mL / min.

[0012] Furthermore, in step 3), the secondary calcination temperature is 900℃, the calcination time is 1h, the heating rate is 10℃ / min, and the nitrogen flow rate is 50mL / min.

[0013] Furthermore, the sulfur-doped biochar prepared by the method described above for simultaneously removing large quantities of nanoplastics and antibiotics is also described.

[0014] Furthermore, the sulfur-doped biochar is used in the simultaneous removal of composite pollutants of nanoplastics and antibiotics from water.

[0015] Furthermore, sulfur-doped biochar was added to a complex polluted water body containing nanoplastics and antibiotics, and the two types of pollutants were removed simultaneously by stirring at room temperature.

[0016] Furthermore, the nanoplastic is selected from at least one of polystyrene, polymethyl methacrylate, polyethylene, and polyvinyl chloride; the antibiotic includes cephalosporins, sulfonamides, and quinolones.

[0017] Furthermore, the sulfur-doped biochar has an adsorption capacity of 60-300 mg / g for nanoplastics and an adsorption capacity of 2.5-5 mmol / g for antibiotics.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] (1) The sulfur-doped modified biochar of the present invention is a novel and original preparation system. The raw materials used for preparation are only three types of low-cost materials: agricultural and forestry waste rice straw, sodium thiosulfate pentahydrate, and potassium bicarbonate. The solid waste straw is used as the core substrate to realize the resource utilization of agricultural and forestry waste. The overall preparation yield of the material is close to 60%, which is significantly better than many existing high-temperature pyrolysis engineering carbon or biochar. The raw material utilization rate is high, and the production process does not require precious metals, heavy metals, or other expensive or toxic reagents. The preparation cost is low and it is easy to carry out large-scale production.

[0020] (2) The sulfur-doped biochar of this invention exhibits extremely strong adsorption affinity and ultra-high saturated adsorption capacity for various nanoplastics and antibiotics. Comparative experiments have verified that, under the same water environment conditions, its adsorption capacity for antibiotics is 1.3 to 1.6 times that of the control group of homologous biochar, specifically 1.6 times that of undoped pyrolytic straw biochar (PBC) and 1.3 times that of nitrogen-doped pyrolytic straw biochar (NPBC). That is, the sulfur doping strategy in this application can further significantly improve the pollution purification capacity of biochar based on common biochar modification methods (such as graphitization, pore expansion, and nitrogen doping). Compared with carbon materials in the literature, the sulfur-doped biochar in this application can efficiently capture nanoplastics with different structures and polycyclic / heterocyclic antibiotics, with a wide range of applicable pollutants. The adsorption capacity, converted into molar equivalents, can reach 2 to 5 mmol / g and several hundred to 1000 mg / g, which belongs to the ultra-high adsorption capacity level.

[0021] (3) The sulfur-doped biochar of the present invention is also resistant to the negative interference of salt, humus and heavy metals, has stable adsorption performance in complex water bodies, and has no secondary pollution caused by the leaching of toxic substances. It is suitable for the deep purification of various wastewaters. It can remove micro-nano plastics and antibiotics at the same time. There is no obvious competition between the two and there is synergistic adsorption. It can treat composite pollutants in an integrated manner, thereby simplifying the process and reducing water treatment costs.

[0022] (4) The sulfur-doped biochar prepared by this invention can regulate the electron distribution of the graphite carbon skeleton by doping with sulfur atoms, and introduce more hydrophilic sulfur-containing and oxygen-containing group sites, so that the material surface forms multiple affinity adsorption sites such as hydrogen bonds, electrostatics, hydrophobicity, and π-π electron donors and acceptors. Multiple forces work together to achieve the capture effect, which can efficiently adapt to the capture of heterocyclic antibiotic molecules with significant differences in structure and nanoplastics with multiple polymer chains, rather than using single forces such as pore interception, electrostatics, and hydrophobicity as common adsorption technologies. Thus, from the mechanism level, it ensures high-capacity and high-efficiency adsorption performance. Attached Figure Description

[0023] Figure 1 SEM images of biochar prepared in Examples 1-3 of this application; where a is PBC, b is NPBC, and c is SPBC;

[0024] Figure 2XPS spectra of SPBC and NPBC in this application;

[0025] Figure 3 This is a comparison chart of the equilibrium adsorption capacities of different modified biochars for four classes of antibiotics in this application;

[0026] Figure 4 This is a comparison chart showing the influence of different coexisting substrates in different water bodies on the adsorption rates of CEC and AMX antibiotics by SPBC in this application.

[0027] Figure 5 This is a comparison chart of the equilibrium adsorption capacity of biochar prepared in Examples 1-3 of this application for three types of nanoplastics: PVC, PS, and PMMA.

[0028] Figure 6 This is a graph showing the influence of different coexisting water substrates on the equilibrium capacity of SPBC adsorption of PVC nanoplastics in this application.

[0029] Figure 7 This is a comparison of (a) the effect of SPBC on antibiotic adsorption when different nanoplastics coexist and (b) the effect of SPBC on the adsorption and removal of nanoplastics when different antibiotics coexist;

[0030] Figure 8 The image shows an electron microscope image of SPBC after simultaneous adsorption and removal of PVC and CEC in (a) and (b) of this application. Detailed Implementation

[0031] The present invention will be further illustrated below with reference to specific embodiments. These embodiments are implemented based on the technical solutions of the present invention, and it should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0032] The adsorption capacity in the following examples ( The formula for calculating (mg / g or mmol / g) is:

[0033]

[0034] in, (mg / g or mmol / g) represents the equilibrium adsorption capacity of SPBC for the target pollutant, C0 (mg / L or mmol / L) and C e (mg / L or mmol / L) represent the initial concentration of the target pollutant and the remaining concentration in the solution after adsorption equilibrium, respectively. V (L) represents the solution volume of the pollutant, and m (g) represents the mass of SPBC added.

[0035] The formula for calculating the adsorption rate (η, %) is:

[0036]

[0037] Where η (%) represents the adsorption and removal rate of the target pollutant by SPBC, and C0 (mg / L or mmol / L) and C t (mg / L or mmol / L) represent the initial concentration of the target pollutant and the remaining concentration in the solution at time t, respectively.

[0038] Example 1

[0039] Rice straw was crushed and passed through a 20-mesh sieve. 30g of the sieved straw powder was then ball-milled in a planetary ball mill at 500 rpm for 5 hours. The ball-milled straw powder and KHCO3 were ground and mixed evenly at a mass ratio of 1:2. The mixture was then calcined in a tube furnace at 900℃ for 2 hours under a N2 atmosphere (heating rate 5℃ / min, N2 flow rate 50mL / min), and cooled to room temperature. The calcined product was washed with 1L of pure water, filtered, and repeated 5 times. After washing, it was dried in an oven at 60℃. The dried carbon was then calcined a second time at 900℃ for 1 hour (heating rate 10℃ / min, N2 flow rate 50mL / min) to obtain unadulterated biochar (PBC).

[0040] Example 2

[0041] Rice straw was crushed and passed through a 20-mesh sieve. 30g of the sieved straw powder was then ball-milled in a planetary ball mill at 500 rpm for 5 hours. The ball-milled straw powder, sodium thiosulfate pentahydrate, and KHCO3 were ground and mixed evenly at a mass ratio of 1:1:2. The mixture was then calcined in a tube furnace at 900℃ for 2 hours under a N2 atmosphere (heating rate 5℃ / min, N2 flow rate 50 mL / min). After cooling to room temperature, the calcined product was washed with 1L of pure water, filtered, and repeated 5 times. After washing, the product was dried in an oven at 60℃. The dried carbon was then calcined a second time at 900℃ for 1 hour (heating rate 10℃ / min, N2 flow rate 50 mL / min) to obtain sulfur-doped biochar (SPBC).

[0042] Example 3

[0043] Rice straw was crushed and passed through a 20-mesh sieve. 30g of the sieved straw powder was then ball-milled in a planetary ball mill at 500 rpm for 5 hours. The ball-milled straw powder, urea, and KHCO3 were ground and mixed evenly at a mass ratio of 1:1:2. The mixture was then calcined in a tube furnace at 900℃ for 2 hours under a N2 atmosphere (heating rate 5℃ / min, N2 flow rate 50mL / min). After cooling to room temperature, the calcined product was washed with 1L of pure water, filtered, and repeated 5 times. After washing, the product was dried in an oven at 60℃. The dried carbon was then calcined a second time at 900℃ for 1 hour (heating rate 10℃ / min, N2 flow rate 50mL / min) to obtain nitrogen-doped biochar (NPBC).

[0044] Depend on Figure 1SEM images of biochar prepared in Examples 1-3 show that, as shown in (a), the original doped biochar PBC has irregular pore walls and a relatively messy surface. As shown in (b), the nitrogen-doped NPBC exhibits a honeycomb-like surface. As shown in (c), the sulfur-doped SPBC displays a looser honeycomb outer surface, with relatively regular pore walls and localized fragmentation. Under high-magnification electron microscopy, dense nanoscale etched pores can be clearly observed on its surface. Figure 1 c) This ample exposure provides an extremely rich internal and external contact area for the adhesion of pollutants.

[0045] Depend on Figure 2 XPS spectra of SPBC and NPBC show that the SPBC surface is dominated by CC / C=C structures, indicating a high degree of aromatization and graphitization, which is beneficial for improving material stability, electron transport capacity, and π–π interaction capabilities with organic pollutants. The SPBC surface contains oxygen-containing functional groups such as CO, OC=O, and C=O, which can provide hydrogen bonding, electrostatic, and polar adsorption sites. The presence of CSC and SOx characteristic peaks in the S2p spectrum indicates that sulfur has been successfully introduced into the carbon framework and surface structure, forming sulfur-containing active sites. The NPBC surface contains nitrogen-containing structures such as pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen, and nitrogen oxides, which can provide certain polar functional groups and interfacial interaction sites.

[0046] As shown in Table 1, the specific surface area (SBET) of PBC is 2275.38 m². 2 / g, and possesses the highest microporous specific surface area (553.05m²) among the three. 2 The presence of numerous native micropores generated during high-temperature activation ( / g) indicates that the structure retains a large number of these micropores. After heteroatom doping, the specific surface areas of both NPBC and SPBC increased significantly compared to PBC, reaching 3124.86 m². 2 / g and 3137.87m 2 / g. Furthermore, with the surge in specific surface area, the micropore volume of both NPBC and SPBC showed a decreasing trend, while the average pore size expanded from 3.02 nm for PBC to 3.26 nm (NPBC) and 3.70 nm (SPBC), respectively. The total pore volume of SPBC more than doubled, reaching 2.90 cm³. 3 / g.

[0047] Table 1. Physicochemical parameters of pore structure of different modified straw biochar

[0048]

[0049] Example 4

[0050] Solutions of cephalexin (CEX), cefaclor (CEC), amoxicillin (AMX), and ampicillin (AMP) with concentrations of 1 mmol / L were prepared and sonicated to ensure complete dissolution and homogeneity. 5 mg of PBC (undoped biochar), SPBC (sulfur-doped biochar), and NPBC (nitrogen-doped biochar) were accurately weighed and placed in separate 30 mL glass bottles (each adsorbent corresponds to one of the four antibiotic solutions). Then, 20 mL of the corresponding antibiotic solution was added to each bottle. The bottles were sealed and placed in a constant-temperature shaker at room temperature and 200 rpm for 24 h for adsorption. Samples were filtered through a 0.22 μm filter, diluted, and the absorbance was measured at the maximum absorption wavelength using a UV-Vis spectrophotometer. The concentrations of the antibiotics in the solutions before and after adsorption were calculated based on the standard curve, and the adsorption amount and removal rate were calculated from the concentration difference. Results are shown below. Figure 3 .

[0051] Depend on Figure 3 It was found that SPBC exhibited superior adsorption capacity for all four antibiotics (CEC, CEX, AMX, and AMP) compared to PBC and NPBC, demonstrating the best overall adsorption performance. The adsorption of CEC was the most significant, with SPBC achieving an adsorption capacity of approximately 4.1 mmol / g (1508.0 mg / g), while PBC and NPBC achieved approximately 2.6 mmol / g and 3.4 mmol / g, respectively. SPBC's adsorption capacity was approximately 1.6 times that of PBC and 1.2 times that of NPBC. For CEX, AMX, and AMP, SPBC's adsorption capacity also reached approximately 2.8 mmol / g (972.7 mg / g), 2.5 mmol / g (913.5 mg / g), and 2.8 mmol / g (978.3 mg / g), respectively, all significantly higher than the other two biochar types. This indicates that sulfur doping, based on common graphitization and pore-expanding modifications, can further and significantly enhance the adsorption capacity of biochar for these antibiotics. Furthermore, sulfur doping shows better application potential in antibiotic pollution removal compared to the more commonly reported nitrogen doping strategies.

[0052] Example 5

[0053] 5 mg of SPBC was weighed and placed in a 30 mL glass bottle. 20 mL of ANTs solution (CEC, AMX) was added to maintain an initial ANTs concentration of 1 mmol / L. Magnesium chloride (MgCl2, 10 mmol / L), sodium sulfate (Na2SO4, 10 mmol / L), humic acid (HA, 10 mg / L), and copper sulfate (CuSO4, 10 mmol / L) were added for adsorption for 24 h. Samples were filtered through a 0.22 μm filter, diluted, and the absorbance was measured at the maximum absorption wavelength using a UV-Vis spectrophotometer. The concentration of antibiotics in the solution before and after adsorption was calculated based on the standard curve. The adsorption amount and removal rate were calculated from the concentration difference. Results are shown below. Figure 4 .

[0054] MgCl2 and Na2SO4 are representative of common inorganic salts in water bodies, while HA is representative of common natural organic matter in water bodies. Figure 4 It can be seen that high salt significantly promotes the adsorption of antibiotics by SPBC; the coexistence of HA has only a slight inhibitory effect on the removal of antibiotics by SPBC, with an inhibition rate of less than 7%, and overall it has better interference resistance.

[0055] Example 6

[0056] Suspensions of polystyrene (PS), polyvinyl chloride (PVC), and polymethyl methacrylate (PMMA) nanoplastics with a concentration of 60 ppm were prepared (all stock solutions were purchased from Jiangsu Zhichuan Technology Co., Ltd.), and ultrasonically dispersed to ensure uniform dispersion. 5 mg of SPBC, PBC, and NPBC were accurately weighed and placed in separate 30 mL glass bottles (each adsorbent corresponds to one of the three nanoplastic suspensions). Then, 20 mL of the corresponding nanoplastic suspension was added to each bottle. The bottles were sealed and placed in a constant-temperature shaker at room temperature and 200 rpm for 24 h for adsorption. Samples were filtered through a 1 μm filter, diluted, and fluorescence intensity was measured using a transient steady-state fluorescence spectrometer. The adsorption capacity and removal rate were calculated based on the difference in fluorescence intensity before and after adsorption. Results are shown below. Figure 5 .

[0057] Depend on Figure 5 It was found that, under the condition of 60 ppm nanoplastic concentration, the adsorption capacities of SPBC for PVC, PS, and PMMA were 198.2, 240.3, and 139.1 mg / g, respectively, all significantly higher than those of PBC and NPBC. Specifically, compared to PBC, SPBC showed adsorption capacities for PVC, PS, and PMMA that were increased by 35.5%, 27.2%, and 77.2%, respectively, demonstrating superior nanoplastic adsorption performance. This indicates that sulfur doping can effectively enhance the utilization rate of active sites on the biochar surface and strengthen the interfacial interaction between it and nanoplastics, thereby endowing SPBC with higher affinity and a broader spectrum of nanoplastic removal potential.

[0058] Example 7

[0059] PVC fluorescent microsphere stock solution (10 mg / mL, average particle size 100 nm) was ultrasonically dispersed and then diluted to prepare a 60 ppm working solution. 10 mmol / L sodium chloride (NaCl), sodium sulfate (Na₂SO₄), 10 mg / L humic acid (HA), copper sulfate solution (CuSO₄), and a blank control group without interfering components were added to the PVC fluorescent microsphere working solution. Then, 5 mg of SPBC was added and the volume was adjusted to 20 mL. Adsorption reaction was carried out under the same shaking conditions. Samples were taken, filtered through a 1 μm filter membrane, diluted, and the fluorescence intensity was measured. The influence of common background matrices on the adsorption process was analyzed by comparing the changes in adsorption capacity under different salt systems. Results are shown below. Figure 6 .

[0060] Depend on Figure 6 It was found that under the coexistence of NaCl, Na2SO4, HA, and CuSO4, the adsorption capacity of SPBC for PVC not only did not decrease compared to the control group, but actually increased by approximately 26.1%, 30.0%, 27.2%, and 25.0%, respectively, indicating that no negative impact was observed. This demonstrates that SPBC exhibits excellent stability in the large-capacity removal of nanoplastics, is suitable for complex polluted water conditions containing salt, organic matter, and heavy metals, and can maintain stable and efficient nanoplastic removal performance even in complex water environments.

[0061] Example 8

[0062] The simultaneous removal performance of nanoplastics and antibiotics as combined pollutants was observed. The effect of antibiotics on nanoplastic removal was investigated: CEC antibiotic solutions with a concentration of 1.0 mmol / L and PVC, PS, and PMMA nanoplastic suspensions with a concentration of 60 ppm were prepared. 5 mg of SPBC was accurately weighed into a 30 mL glass bottle. 20 mL of CEC solution (control group) and 20 mL of mixed solutions containing CEC (1.0 mmol / L) and different nanoplastics (60 ppm) were added to each system (CEC-PVC, CEC-PS, and CEC-PMMA groups). The glass bottles were sealed and placed in a constant-temperature shaker for 24 h for adsorption. After adsorption equilibrium was reached, samples were taken, filtered through a 0.22 μm filter membrane, diluted, and the absorbance was measured at the maximum absorption wavelength using a UV-Vis spectrophotometer. The concentration of antibiotics in the solution before and after adsorption was calculated based on the standard curve, and the adsorption amount and removal rate were calculated from the concentration difference. Results are shown below. Figure 7 a.

[0063] Example 9

[0064] The simultaneous removal performance of nanoplastics and antibiotics as composite pollutants was observed. The effect of nanoplastics on antibiotic removal was investigated: A 60 ppm PVC nanoplastic suspension and 1.0 mmol / L solutions of CEC, AMX, and AMP antibiotics were prepared. 5 mg of SPBC was accurately weighed into a 30 mL glass bottle. 20 mL of PVC suspension (control group) and 20 mL of mixed solutions containing PVC (60 ppm) and different antibiotics (1.0 mmol / L) were added to each system (PVC-CEC, PVC-AMX, and PVC-AMP groups, respectively). The glass bottles were sealed and placed in a constant-temperature shaker for 24 h at room temperature and 200 rpm. Samples were filtered through a 1 μm filter, diluted, and fluorescence intensity was measured using a transient steady-state fluorescence spectrometer. The adsorption amount and removal rate were calculated based on the difference in fluorescence intensity before and after adsorption.

[0065] Depend on Figure 7 It can be seen that the coexistence of nanoplastics and antibiotics has a relatively small impact on their respective adsorption processes. In the presence of PVC, PS, and PMMA, the CEC adsorption capacity decreased by only 2.0%, 7.3%, and 12.0%, respectively, showing no significant competitive adsorption phenomenon; [The text abruptly ends here, likely due to an incomplete sentence or missing information.] Figure 7 As shown in b, the coexistence of CEC promoted the adsorption of PVC by SPBC biochar, with an increase rate of 9.9%. Although the adsorption capacity of PVC decreased by 6.4% and 16.8% respectively when AMX and AMP coexisted, the overall PVC adsorption and removal level remained high. Figure 8 Scanning electron micrographs of SPBC simultaneously trapping antibiotic CEC and nanoplastic PVC are presented. These results indicate that SPBC has a good simultaneous large-capacity removal capability for the antibiotic and nanoplastic composite pollution system. The competitive effect between the two types of pollutants is weak, and some systems even have a synergistic promoting effect, indicating that SPBC can achieve simultaneous large-capacity removal of antibiotic and nanoplastic composite pollutants.

[0066] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing biochar capable of simultaneously and in large capacity removing nanoplastics and antibiotics, characterized in that, Includes the following steps: 1) After washing, drying, crushing and sieving the straw, it is ball-milled using a planetary ball mill to obtain straw powder; 2) Grind and mix straw powder, potassium thiosulfate, and potassium bicarbonate evenly. Place the mixture in a tube furnace and calcine it once under nitrogen atmosphere protection. After cooling, the calcined product is washed, filtered, and dried multiple times. 3) The dried solid product was calcined again under nitrogen protection, and after cooling, sulfur-doped biochar was obtained.

2. The method for preparing biochar capable of simultaneously and in large capacity removing nanoplastics and antibiotics according to claim 1, characterized in that: In step 1), the ball milling speed is 500 r / min and the time is 5 h.

3. The method for preparing biochar capable of simultaneously removing nanoplastics and antibiotics in large quantities according to claim 1, characterized in that: In step 2), the mass ratio of straw powder, potassium thiosulfate and potassium bicarbonate is 1:1:

2.

4. The method for preparing biochar capable of simultaneously removing nanoplastics and antibiotics in large quantities according to claim 1, characterized in that: In step 2), the calcination temperature is 900℃, the calcination time is 2h, the heating rate is 5℃ / min, and the nitrogen flow rate is 50mL / min.

5. The method for preparing biochar capable of simultaneously and in large capacity removing nanoplastics and antibiotics according to claim 1, characterized in that: In step 3), the secondary calcination temperature is 900℃, the calcination time is 1h, the heating rate is 10℃ / min, and the nitrogen flow rate is 50mL / min.

6. Sulfur-doped biochar prepared by the method for preparing biochar capable of simultaneously and in large capacity removing nanoplastics and antibiotics as described in any one of claims 1 to 5.

7. The application of the sulfur-doped biochar according to claim 6 in the simultaneous removal of composite pollutants of nanoplastics and antibiotics from water.

8. The application according to claim 7, characterized in that: Sulfur-doped biochar was added to a complex polluted water body containing nanoplastics and antibiotics, and the two types of pollutants were removed simultaneously by stirring at room temperature.

9. The application according to claim 7, characterized in that: The nanoplastic is selected from at least one of polystyrene, polymethyl methacrylate, polyethylene, and polyvinyl chloride; the antibiotic includes cephalosporins, sulfonamides, and quinolones.

10. The application according to claim 7, characterized in that: The sulfur-doped biochar has an adsorption capacity of 60-300 mg / g for nanoplastics and an adsorption capacity of 2.5-5 mmol / g for antibiotics.